2019
DOI: 10.1002/pa.1954
|View full text |Cite
|
Sign up to set email alerts
|

China–Pakistan Economic Corridor (CPEC) development projects and entrepreneurial potential of locals

Abstract: This research explores a very important issue arising from the initiation of China–Pakistan Economic Corridor (CPEC) in Pakistan, as the major impact seems to be focused towards small businesses and how they will cope in this competitive market once Chinese businesses enter in the country. According to scholars and officials, CPEC will generate several business opportunities for the local Pakistani community. However, studies related to the CPEC project are limited and only focused on the development of the CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(38 citation statements)
references
References 66 publications
1
37
0
Order By: Relevance
“…Local people expect numerous job opportunities and high earning position via CPEC, which can mitigate their poverty [31]. In general, our findings are related to Kanwal et al [30], where several benefits of the CEPC; employment opportunities, poverty reeducation, and social welfare are reported.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Local people expect numerous job opportunities and high earning position via CPEC, which can mitigate their poverty [31]. In general, our findings are related to Kanwal et al [30], where several benefits of the CEPC; employment opportunities, poverty reeducation, and social welfare are reported.…”
Section: Discussionsupporting
confidence: 82%
“…In line with Hansen et al [62], who argued that new projects and international resources create new opportunities for the betterment of people. Moreover, Kanwal et al [30] also revealed that CPEC will significantly expand job the circle of job opportunities for local communities and a common man in Pakistan. Additionally, Chen et al [27] also revealed that CPEC is a mega project and perceived for millions of job in different sectors.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study examined the benefits and advantages of CPEC for women in the rural areas of Pakistan. Although there are several studies that have examined the role of CPEC in economic development, employment and livelihood of citizens [5,7,15]. But, studies to examine how the CEPC would benefit rural women of Pakistan in terms of new opportunities, quality of life and self-enhancement are missing.…”
Section: Discussionmentioning
confidence: 99%
“…In short, the level of safety climate of organization plays an important role in the operation of coal-mine safety production, and the improvement level of safety climate depends on the organization's emphasis and the attention degree on safety [16,17]. According to the theory of social exchange [18][19][20], the safety climate level of organization and the behavioral decision of miners are equivalent and reciprocal. At the same time, the supervision of first-line managers also affects the behavioral decision making of miners.…”
Section: Introductionmentioning
confidence: 99%